Positive electrode active material and lithium secondary battery including the same

By using excess manganese oxide containing lithium containing molybdenum, the problem of insufficient electrochemical characteristics and stability of the cathode material of lithium-ion batteries is solved, and higher discharge capacity and battery life are achieved.

JP2025015605AActive Publication Date: 2025-01-30ECOPRO BM CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024197820
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-10-28
Filing Date
2024-11-13
Publication Date
2025-01-30
Estimated Expiration
2041-11-08

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode active materials have problems with insufficient electrochemical characteristics and stability, especially in high voltage operating environments, with low conductivity and poor circulation characteristics, resulting in a decrease in battery capacity and life efficiency, and the traditional improvement methods have not reached the commercial level.

Method used

Using lithium excess manganese oxides containing lithium, nickel, manganese and molybdenum, the crystal growth of the positive electrode particles is promoted by using a molybdenum-containing flux, increasing the particle size to 0.4 μm to 3.0 μm, reducing the particle transfer effect, and the presence of molybdenum oxides on the surface of the particles to improve lithium ion transport and diffusion.

Benefits of technology

It improves the discharge capacity and electrochemical stability of lithium-ion batteries, reduces voltage attenuation, and improves the cycle life and conductivity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015605000001_ABST
    Figure 2025015605000001_ABST
Patent Text Reader

Abstract

To provide a positive electrode active material including a lithium manganese-based oxide, the positive electrode active material being capable of mitigation and / or prevention of a decrease in charge / discharge capacity or voltage decay during the cycling of a lithium secondary battery using the positive electrode active material.SOLUTION: A positive electrode active material includes a lithium-rich lithium manganese-based oxide containing at least lithium, nickel, manganese and molybdenum. The lithium manganese-based oxide includes at least one primary particle. The average particle diameter of the primary particle in the lithium manganese-based oxide is 0.4 to 3.0 μm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material and a lithium secondary battery including the same, and more specifically, to a positive electrode active material and a lithium secondary battery including the same, which comprises a lithium-excess lithium-manganese-based oxide containing at least lithium, nickel, manganese and molybdenum, the lithium-manganese-based oxide including at least one primary particle, and which uses a flux containing molybdenum to improve crystal growth of the primary particle, thereby mitigating and / or preventing a decrease in stability caused by excess lithium and manganese present in the lithium-manganese-based oxide. [Background technology]

[0002] Batteries store electricity by using materials capable of electrochemical reactions at the positive and negative electrodes. A representative example of such batteries is the lithium secondary battery, which stores electrical energy by the difference in chemical potential when lithium ions are intercalated / deintercalated at the positive and negative electrodes.

[0003] The lithium secondary battery is manufactured by using a material capable of reversible intercalation / deintercalation of lithium ions as a positive electrode and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] Lithium composite oxides are used as the positive electrode active material of lithium secondary batteries. Examples of such oxides include LiCoO2, LiMn2O4, LiNiO2, LiMnO2, and composite oxides containing Ni, Co, Mn, Al, etc., as disclosed in Korean Patent Publication No. 10-2015-0069334 (published on June 23, 2015).

[0005] Among the positive electrode active materials, LiCoO2 is the most widely used because of its excellent life characteristics and charge / discharge efficiency. However, it has a drawback in that it is expensive due to the limited availability of cobalt as a raw material, and therefore has limited price competitiveness.

[0006] Lithium manganese oxides such as LiMnO2 and LiMn2O4 have the advantages of being thermally safe and inexpensive, but have problems with small capacity and poor high-temperature characteristics. In addition, LiNiO2-based positive electrode active materials show high discharge capacity battery characteristics, but are difficult to synthesize due to the problem of cation mixing between Li and transition metals, which causes major problems with rate characteristics.

[0007] In addition, a large amount of Li by-products are generated depending on the depth of this cation mixing, and most of these Li by-products consist of compounds of LiOH and Li2CO3, which cause gelation during the manufacture of the positive electrode paste and gas generation during charge and discharge after the electrode is manufactured. The remaining Li2CO3 not only increases the swelling phenomenon of the cell, reducing the cycle, but also causes the battery to swell.

[0008] Various candidate materials for compensating for the shortcomings of conventional positive electrode active materials are being discussed.

[0009] For example, research is being conducted to use lithium-rich lithium manganese oxides, which contain an excess amount of Mn among transition metals and have a lithium content greater than the total content of the transition metals, as a positive electrode active material for lithium secondary batteries. Such lithium-rich lithium manganese oxides are also called overlithiated layered oxides (OLO).

[0010] Although OLO has an advantage of theoretically being able to exhibit high capacity under a high voltage operating environment, it has a disadvantage in that the rate capability of a lithium secondary battery using OLO is low due to its relatively low electrical conductivity caused by the excessive amount of Mn contained in the oxide. If the rate capability is low, there is a problem in that the charge / discharge capacity and life efficiency (capacity retention) decrease during cycling of the lithium secondary battery.

[0011] In addition, the decrease in charge / discharge capacity or voltage decay during cycling of a lithium secondary battery using OLO may be caused by a phase transition due to the movement of transition metals in the lithium manganese oxide. For example, when a phase transition is induced by the movement of transition metals in an unintended direction in a lithium manganese oxide having a layered crystal structure, a spinel or similar crystal structure may be formed entirely and / or partially in the lithium manganese oxide.

[0012] There have been attempts to solve the above problems with OLO through particle structure improvement and surface modification, such as adjusting the particle size or coating the surface of OLO, but these efforts have not yet reached a commercial level. Summary of the Invention [Problem to be solved by the invention]

[0013] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles is playing a leading role, and the demand for positive electrode active materials used in lithium secondary batteries is also continuously changing.

[0014] For example, lithium secondary batteries using LFP have traditionally been used primarily for safety reasons, but recently there has been a trend toward expanding use of nickel-based lithium composite oxides, which have a larger energy capacity per weight than LFP.

[0015] In addition, many nickel-based lithium composite oxides that are currently used as positive electrode active materials for high-capacity lithium secondary batteries essentially use ternary metal elements such as nickel, cobalt, and manganese or nickel, cobalt, and aluminum. Among them, cobalt has problems such as unstable supply and demand and is extremely expensive compared to other raw materials, so there is a need for a new positive electrode active material with a reduced cobalt content or that can eliminate cobalt.

[0016] From this perspective, lithium-rich lithium manganese oxide can meet the above market expectations, but the electrochemical properties and stability of lithium manganese oxide are still insufficient to replace the commercially available NCM or NCA type positive electrode active materials.

[0017] However, when compared with other types of commercially available positive electrode active materials, the conventional lithium-excess lithium manganese-based oxide has disadvantages in terms of electrochemical properties and / or stability. However, the present inventors have confirmed that when a molybdenum-containing flux is used to improve the crystal growth of the primary particles constituting the lithium manganese-based oxide (i.e., when the size of the primary particles is increased), the lithium-excess lithium manganese-based oxide can also exhibit electrochemical properties and stability at a level that allows it to be commercially used.

[0018] Accordingly, the present invention provides a positive electrode active material that includes a lithium-excess lithium-manganese-based oxide containing at least lithium, nickel, manganese, and molybdenum, and that uses a flux containing molybdenum to grow crystals such that the average particle size of primary particles in the lithium-manganese-based oxide is 0.4 μm or more, thereby reducing a phase transition effect due to the movement of transition metals between particles, thereby mitigating and / or preventing a decrease in charge / discharge capacity or a voltage decay during cycling of a lithium secondary battery that uses the positive electrode active material containing the lithium-manganese-based oxide.

[0019] Another object of the present invention is to provide a positive electrode active material that can mitigate and / or prevent a decrease in charge-transfer and / or diffusion (i.e., surface kinetics) of Li ions on the surfaces of the primary particles due to an increase in the average particle size of the primary particles in the lithium manganese oxide, by promoting crystal growth of the primary particles in the lithium manganese oxide using a flux containing molybdenum and simultaneously allowing some of the molybdenum to be present in the form of an oxide on the surfaces of the primary particles.

[0020] Another object of the present invention is to provide a lithium secondary battery in which the low discharge capacity of the conventional OLO is improved by using a positive electrode containing the positive electrode active material defined in the present application. [Means for solving the problem]

[0021] According to one aspect of the present invention for solving the above-mentioned technical problems, there is provided a positive electrode active material comprising a lithium-excess lithium-manganese-based oxide that contains at least lithium, nickel, manganese, and molybdenum, the lithium-manganese-based oxide comprising at least one primary particle, and the average particle size of the primary particle in the lithium-manganese-based oxide is 0.4 μm to 3.0 μm.

[0022] In this case, the lithium manganese-based oxide includes primary particles whose crystal growth is promoted by using a molybdenum-containing flux.

[0023] In this case, a portion of the molybdenum contained in the flux may exist as a dopant in the primary particles.

[0024] In one embodiment, the lithium manganese-based oxide may be represented by the following Formula 1:

[0025] [Chemical formula 1] rLi2Mn 1-a Mo a O3·(1-r)Li bNi x Co y Mn z Mo z′ M1 1-(x+y+z+z′) O2

[0026] Where: M1 is at least one selected from Nb, Fe, Cr, V, Cu, Zn, Sn, Mg, Ru, Al, Ti, Zr, B, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si, and Bi; 0 <r≦0.7、0≦a<0.2、0<b≦1、0<x≦1、0≦y<1、0<z<1、0<z′<0.2および0<x+y+z+z′≦1である。

[0027] As shown in Formula 1, the molybdenum present in the lithium manganese-based oxide corresponds to the c2 / m phase, rLi2Mn 1-a Mo a (1-r)Li corresponding to O3 and / or R3-m phase b Ni x Co y Mn z Mo z′ M1 1-(x+y+z+z′) It may be present as a dopant in O2.

[0028] A part of the molybdenum used as a flux for the crystal growth of the primary particles constituting the lithium manganese-based oxide exists as a dopant in the lithium manganese-based oxide, and thus the lithium manganese-based oxide contains excess lithium and manganese, which corresponds to the c2 / m phase. 1-a Mo a Electrical activation of O3 can be induced.

[0029] In addition, a portion of the molybdenum used as a flux for crystal growth of the primary particles constituting the lithium manganese-based oxide is present in the form of an oxide on the surfaces of the primary particles, thereby mitigating and / or preventing a decrease in charge-transfer and / or diffusion (i.e., surface kinetic) of Li ions on the surfaces of the primary particles due to an increase in the average particle size of the primary particles in the lithium manganese-based oxide.

[0030] According to another aspect of the present invention, there is provided a positive electrode comprising the above-described positive electrode active material.

[0031] According to yet another aspect of the present invention, there is provided a lithium secondary battery using the above-mentioned positive electrode. Effect of the Invention

[0032] According to the present invention, it is possible to improve the limitations of conventional lithium-excess lithium manganese-based oxides, which have various disadvantages in terms of electrochemical properties and / or stability, when compared with other types of commercially available positive electrode active materials.

[0033] Specifically, the primary particles constituting the lithium manganese-based oxide according to the present invention can reduce or eliminate the decrease in charge-discharge capacity or voltage decay during cycling of a lithium secondary battery including the lithium manganese-based oxide as a positive electrode active material, as the crystal growth is promoted by using a flux containing molybdenum.

[0034] In addition, a part of the molybdenum used as a flux for the crystal growth of the primary particles constituting the lithium manganese-based oxide exists as a dopant in the lithium manganese-based oxide, and thus the lithium manganese-based oxide has a c2 / m phase containing excess lithium and manganese. 1-a Mo aBy inducing electrical activation of O3, it is possible to improve the discharge characteristics, such as the average discharge voltage retention rate and the rate of discharge capacity, of a lithium secondary battery using the lithium manganese-based oxide as a positive electrode active material.

[0035] In addition, a portion of the molybdenum used as a flux for crystal growth of the primary particles constituting the lithium manganese-based oxide is present in the form of an oxide on the surfaces of the primary particles, thereby mitigating and / or preventing a decrease in charge-transfer and / or diffusion (i.e., surface kinetic) of Li ions on the surfaces of the primary particles due to an increase in the average particle size of the primary particles in the lithium manganese-based oxide. [Brief description of the drawings]

[0036] [Figure 1] 2 is a SEM image of a lithium manganese-based oxide contained in the positive electrode active material according to Example 1. [Diagram 2] 1 is a SEM image of a lithium manganese-based oxide contained in a positive electrode active material according to Comparative Example 1. [Diagram 3] 1 is a SEM image of a lithium manganese-based oxide contained in a positive electrode active material according to Comparative Example 2. [Figure 4] 2 is a cross-sectional SEM image of a lithium manganese-based oxide contained in the positive electrode active material according to Example 1. [Diagram 5] This is an image of molybdenum mapping on the cross-sectional SEM image of Figure 4 through EDX analysis. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0037] In order to make the present invention easier to understand, certain terms are defined herein for convenience. Unless otherwise defined herein, scientific and technical terms used in the present invention shall have the meanings commonly understood by those of ordinary skill in the art. Furthermore, unless otherwise specified by the context, singular terms shall be understood to include their plural forms, and plural terms shall be understood to include their singular forms.

[0038] Hereinafter, a positive electrode active material including a lithium-excess lithium-manganese-based oxide including at least lithium, nickel, manganese, and molybdenum according to the present invention and a lithium secondary battery including the positive electrode active material will be described in more detail.

[0039] positive electrode active material According to one aspect of the present invention, there is provided a positive electrode active material comprising a lithium-rich lithium manganese-based oxide that contains at least lithium, nickel, manganese, and molybdenum. The lithium manganese-based oxide is a composite metal oxide capable of intercalating and deintercalating lithium ions.

[0040] The lithium manganese-based oxide included in the positive electrode active material defined herein may be a particle including at least one primary particle. When the lithium manganese-based oxide includes a particle formed by agglomeration of a plurality of primary particles, the particle formed by agglomeration of a plurality of primary particles may be referred to as a secondary particle.

[0041] Here, the term "particles including at least one primary particle" should be interpreted as including both "particles formed by agglomeration of a plurality of primary particles" and "non-agglomerated particles including a single primary particle." In this regard, it is preferable that the smaller the number of primary particles constituting the whole particle, the larger the size of the primary particle.

[0042] The primary particles and the secondary particles may each independently have a rod-like, elliptical and / or irregular shape.

[0043] In this case, the lithium manganese-based oxide preferably has an average particle size of 0.4 μm to 3.0 μm, the average particle size being measured as the length of the major axis or minor axis of the primary particle, or as a cumulative average particle size.

[0044] Generally, in conventional OLO, which is a secondary particle formed by agglomeration of a plurality of primary particles, the primary particles have an average particle size of only several to several tens of nm. In contrast, in the lithium manganese-based oxide defined in the present invention, the primary particles have an average particle size of at least 0.4 μm, thereby reducing a phase transition effect caused by the movement of transition metal between particles, and mitigating and / or preventing a decrease in charge / discharge capacity or voltage decay during cycling of a lithium secondary battery using a positive electrode active material including the lithium manganese-based oxide.

[0045] There are various methods for promoting the crystal growth of the primary particles in the lithium manganese oxide, but according to the present invention, the average particle size of the primary particles constituting the lithium manganese oxide may be one in which crystal growth is promoted using a flux containing molybdenum. When the crystal growth of the primary particles is promoted using a flux containing molybdenum, a part of the molybdenum used as the flux may be present as a dopant in the primary particles.

[0046] Meanwhile, when the average particle size of the primary particles in the lithium manganese-based oxide is increased by simply increasing the roasting or sintering temperature during the process of preparing the lithium manganese-based oxide to promote the crystal growth of the particles, the phase transition effect due to the movement of transition metal between particles may not be sufficiently prevented, or the size of the primary particles may become larger than necessary, resulting in a decrease in charge-transfer and / or diffusion (i.e., surface kinetic) of Li ions on the particle surface.

[0047] When the average particle size of the primary particles is less than 0.4 μm, it is difficult to sufficiently reduce or eliminate the decrease in charge / discharge capacity or voltage decay during cycling of a lithium secondary battery including the lithium manganese-based oxide as a positive electrode active material. On the other hand, when the average particle size of the primary particles is more than 3.0 μm, the average particle size of the primary particles becomes too large, which reduces the charge-transfer and / or diffusion (i.e., surface kinetic) of Li ions on the surface of the primary particles, and thus the initial charge / discharge capacity may be rapidly reduced.

[0048] The average particle size of the secondary particles may vary depending on the number of primary particles constituting the secondary particles, but may generally be 1 μm to 30 μm.

[0049] The lithium manganese-based oxide defined herein may be represented by the following Chemical Formula 1:

[0050] [Chemical formula 1] rLi2Mn 1-a Mo a O3·(1-r)Li b Ni x Co y Mn z Mo z′ M1 1-(x+y+z+z′) O2

[0051] Where: M1 is at least one selected from Nb, Fe, Cr, V, Cu, Zn, Sn, Mg, Ru, Al, Ti, Zr, B, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si, and Bi; 0 <r≦0.7、0≦a<0.2、0<b≦1、0<x≦1、0≦y<1、0<z<1、0<z′<0.2および0<x+y+z+z′≦1である。

[0052] The lithium manganese-based oxide represented by Chemical Formula 1 may selectively contain cobalt. In addition, when the lithium manganese-based oxide contains cobalt, the ratio of the number of moles of the cobalt to the number of moles of all metal elements in the lithium manganese-based oxide may be 10% or less, preferably 5% or less. Meanwhile, the lithium manganese-based oxide represented by Chemical Formula 1 may not contain cobalt.

[0053] The lithium manganese oxide represented by the formula 1 is rLi2Mn 1-a Mo a Oxides belonging to the C2 / m space group represented by O3 (hereafter referred to as the "C2 / m phase") and (1-r)Li b Ni x Co y Mn z Mo z′ M1 1-(x+y+z+z′) It is a complex oxide in which oxides of a phase belonging to the R3-m space group represented by O2 (hereinafter referred to as the "R3-m phase") coexist. In this case, the oxides of the C2 / m phase and the oxides of the R3-m phase exist in the form of a solid solution.

[0054] In the lithium manganese-based oxide represented by Formula 1, when r exceeds 0.8, the proportion of Li2MnO3, which is an oxide of the C2 / m phase, in the lithium manganese-based oxide becomes excessively high, and the discharge capacity of the positive active material may decrease. That is, in order to improve the surface kinetics by sufficiently activating the oxide of the C2 / m phase, which has a relatively high resistance in the lithium manganese-based oxide, it is preferable that the oxide of the R3-m phase exists at a predetermined proportion or more.

[0055] In the lithium manganese oxide represented by Chemical Formula 1, molybdenum is preferably present in a range of 0.02 mol % to 5.0 mol % based on the total metal elements excluding lithium.

[0056] The fact that the molybdenum content in the lithium manganese-based oxide is less than 0.02 mol% based on the total metal elements excluding lithium means that the amount of molybdenum-containing flux used for crystal growth of primary particles constituting the lithium manganese-based oxide is insufficient, and the effect of the molybdenum-containing flux on the crystal growth of the primary particles is small.

[0057] In addition, when the content of molybdenum in the lithium manganese oxide is excessively high, the content of active metal elements in the lithium manganese oxide is decreased, which may result in a decrease in the discharge capacity of the positive electrode active material.

[0058] If the amount of molybdenum-containing flux used for crystal growth of the primary particles constituting the lithium manganese-based oxide is insufficient, the average particle size of the primary particles constituting the lithium manganese-based oxide may be smaller than 0.4 μm, or the ratio of primary particles having a particle size smaller than 0.4 μm in the lithium manganese-based oxide may increase.

[0059] This may induce a phase transition due to unintended migration of intergranular transition metals in the lithium manganese-based oxide, which may result in the formation of a spinel or a similar crystal structure entirely and / or partially in the lithium manganese-based oxide.

[0060] The occurrence of such an internal phase transition in the lithium manganese-based oxide acts as a major cause of a decrease in charge-discharge capacity or voltage decay during cycling of a lithium secondary battery using a positive electrode active material including the lithium manganese-based oxide.

[0061] The fact that the molybdenum content in the lithium manganese-based oxide is greater than 5.0 mol% based on the total metal elements excluding lithium means that the amount of molybdenum-containing flux used for crystal growth of primary particles constituting the lithium manganese-based oxide is excessively large.

[0062] In this case, excessive use of the molybdenum-containing flux may cause the crystal growth of the primary particles to become unnecessarily large, which may result in a decrease in charge-transfer and / or diffusion (i.e., surface kinetic) of Li ions on the surfaces of the primary particles.

[0063] In addition, as the content of molybdenum in the lithium manganese-based oxide increases, the proportion of active metal elements that can contribute to improving the initial charge / discharge capacity of a lithium secondary battery using the lithium manganese-based oxide as a positive electrode active material may decrease.

[0064] Even when the crystal growth of the primary particles is promoted using the molybdenum-containing flux, the compressed density of the positive electrode active material under a pressure of 4.5 tons may be 2.8 g / cc or more.

[0065] In the lithium manganese oxide, if the size of the primary particles is too small or too large, the structural stability of the positive electrode active material may be reduced. In addition, in the lithium manganese oxide, if the size of the primary particles is too large, the porosity within the secondary particles increases, and the structural stability of the positive electrode active material may be reduced.

[0066] However, as described above, in the cathode active material according to the present invention, the average particle size of the primary particles in which crystal growth is promoted using a flux containing molybdenum is in the range of 0.4 μm to 3.0 μm, thereby preventing the structural stability of the cathode active material from being reduced.

[0067] In another embodiment, at least one metal oxide represented by the following chemical formula 2 may be present on at least a part of the surface of the lithium manganese-based oxide. In this case, the region where the metal oxide is present may be at least a part of the surface of the primary particles and / or the secondary particles.

[0068] [Chemical formula 2] Li d M2 e O f

[0069] Where: M2 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd; 0≦d≦8, 0 <e≦8、2≦f≦13である。

[0070] The metal oxide represented by Formula 2 may be formed by reacting at least a portion of the metal elements (nickel, manganese, cobalt and / or doping metal) constituting the lithium manganese-based oxide with Li present on the surface of the lithium manganese-based oxide.

[0071] The metal oxide reduces lithium-containing impurities (or residual lithium) present on the surface of the lithium manganese-based oxide and acts as a diffusion path for lithium ions, thereby improving the electrochemical properties of the lithium manganese-based oxide.

[0072] The metal oxide may include at least one selected from molybdenum oxide and lithium molybdenum oxide.

[0073] A portion of the molybdenum used as a flux for crystal growth of the primary particles constituting the lithium manganese-based oxide is present in the form of an oxide on the surfaces of the primary particles, thereby mitigating and / or preventing a decrease in charge-transfer and / or diffusion (i.e., surface kinetic) of Li ions on the surfaces of the primary particles due to an increase in the average particle size of the primary particles in the lithium manganese-based oxide.

[0074] When the lithium manganese-based oxide is a core-shell particle, the metal oxide may be present integrally with the shell.

[0075] As a result, the metal oxide may be present on at least a portion of the surface of the crystallites, primary particles and / or secondary particles that constitute the lithium manganese-based oxide.

[0076] The metal oxide is an oxide of lithium and an element represented by M2 in a composite form, or an oxide of M3. The metal oxide is, for example, Li a W b O c , Li a Zr b O c , Li a Ti b O c , Li a Ni b O c , Li a Co b O c , Li a Al b O c , Li a Mo b O c , Co b O c , Al b O c , W b O c , Zr b O c or Ti b O c However, the above examples are merely given for convenience in order to facilitate understanding, and the metal oxide defined in the present application is not limited to the above examples.

[0077] The metal oxide may be an oxide in which lithium and at least two elements represented by M2 are combined, or may further include an oxide in which lithium and at least two elements represented by M2 are combined. The oxide in which lithium and at least two elements represented by M2 are combined may be, for example, Li a (W / Ti)b O c , Li a (W / Zr) b O c , Li a (W / Ti / Zr) b O c , Li a (W / Ti / B) b O c It may be, but is not necessarily limited to, this.

[0078] Lithium secondary battery According to another aspect of the present invention, there is provided a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer may include the lithium composite oxide according to any of the various embodiments of the present invention as a positive electrode active material.

[0079] Therefore, a detailed description of the lithium composite oxide will be omitted, and only the remaining components not described above will be described below. Also, for convenience, the lithium composite oxide will be referred to as a positive electrode active material hereinafter.

[0080] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may usually have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0081] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition containing the positive electrode active material, a conductive material, and optionally a binder, on the positive electrode current collector.

[0082] At this time, the positive electrode active material may be included in an amount of 80 to 99 wt%, more specifically, 85 to 98.5 wt%, based on the total weight of the positive electrode active material layer. When included in this content range, excellent capacity characteristics can be exhibited, but the amount is not necessarily limited thereto.

[0083] The conductive material is used to impart electrical conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon-based materials such as carbon fibers, metal powders or metal fibers such as copper, nickel, aluminum, and silver, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.

[0084] The binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and among these, one type alone or a mixture of two or more types may be used. The binder may be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.

[0085] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent to prepare a positive electrode slurry composition, which is then coated on a positive electrode current collector, followed by drying and rolling.

[0086] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.

[0087] In another embodiment, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the positive electrode slurry composition from the support, and laminating the resulting film on a positive electrode current collector.

[0088] According to yet another aspect of the present invention, there may be provided an electrochemical device including the above-mentioned positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0089] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Here, since the positive electrode is as described above, a detailed description thereof will be omitted for convenience, and only the remaining components not described above will be described in detail below.

[0090] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0091] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0092] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0093] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition containing the negative electrode active material, a conductive material, and optionally a binder, on the negative electrode current collector.

[0094] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys, and SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide, or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, may be used. A metallic lithium thin film may be used as the negative electrode active material. Low-crystalline carbon and high-crystalline carbon may both be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0095] The negative electrode active material may be included in an amount of 80 to 99 wt % based on the total weight of the negative electrode active material layer.

[0096] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be added in an amount of usually 0.1 to 10 wt% based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0097] The conductive material may be added as a component for further improving the conductivity of the negative electrode active material in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and may be, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride, aluminum, or nickel powder, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, or conductive materials such as polyphenylene derivatives.

[0098] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating. Alternatively, the negative electrode slurry composition may be cast on a separate support, and then peeled off from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0099] In another embodiment, the negative electrode active material layer may be manufactured by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support and peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0100] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used. In addition, in order to ensure heat resistance or mechanical strength, a separator coated with a ceramic component or a polymer material may be used, and may be selectively used as a single-layer or multi-layer structure.

[0101] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0102] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0103] The organic solvent may be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the performance of the electrolyte may be excellent if the cyclic carbonate and the chain carbonate are mixed at a volume ratio of about 1:1 to about 1:9.

[0104] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3), LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably used within a range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that excellent electrolyte performance can be exhibited and lithium ions can be effectively transferred.

[0105] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5% by weight based on the total weight of the electrolyte.

[0106] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0107] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, etc. Furthermore, the lithium secondary battery can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a plurality of battery cells.

[0108] According to yet another aspect of the present invention, there may be provided a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same.

[0109] The battery module or the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (Electric Vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV), or a power storage system.

[0110] The present invention will be described in more detail below with reference to examples. However, these examples are for the purpose of illustrating the present invention, and the scope of the present invention is not to be construed as being limited by these examples.

[0111] Production Example 1. Production of positive electrode active material Example 1 (a) Preparation of precursor The reactor was filled with a mixed aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60, and NaOH and NH4OH were added while stirring. The temperature inside the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while N2 gas was added to the reactor. After the reaction was completed, the mixture was washed and dehydrated, and the Ni 0.4 Mn 0.6 A hydroxide precursor with the composition (OH)2 was obtained.

[0112] (b) First heat treatment The temperature of the calcination furnace in an O2 atmosphere was increased at a rate of 2°C / min, and the hydroxide precursor obtained in step (a) was heat-treated for 5 hours while maintaining the temperature at 550°C. The hydroxide precursor was then cooled in the furnace to obtain an oxide precursor.

[0113] (c) Second heat treatment The oxide precursor obtained in step (b) was mixed with LiOH (Li / (metal excluding Li) molar ratio=1.3) as a lithium compound, and 0.5 mol % of MoO3 based on the total metal elements in the precursor to prepare a mixture.

[0114] Next, the mixture was heat-treated for 8 hours while maintaining the temperature at 1,000°C in a sintering furnace in an O2 atmosphere at a rate of 2°C / min, and then cooled in the furnace to finally obtain a positive electrode active material including a lithium manganese-based oxide.

[0115] Example 2 A positive electrode active material was prepared in the same manner as in Example 1, except that 6.0 mol % of MoO3 was used in step (c).

[0116] Example 3 A positive electrode active material was prepared in the same manner as in Example 1, except that 0.01 mol % of MoO3 was used in step (c).

[0117] Comparative Example 1 A positive electrode active material was prepared in the same manner as in Example 1, except that MoO3 was not used in step (c).

[0118] Comparative Example 2 (a) Preparation of precursor The reactor was filled with a mixed aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60, and NaOH and NH4OH were added while stirring. The temperature inside the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while N2 gas was added to the reactor. After the reaction was completed, the mixture was washed and dehydrated, and the Ni 0.4 Mn0.6 A hydroxide precursor with the composition (OH)2 was obtained.

[0119] (b) First heat treatment The temperature of the calcination furnace in an O2 atmosphere was increased at a rate of 2°C / min, and the hydroxide precursor obtained in step (a) was heat-treated for 5 hours while maintaining the temperature at 800°C. The hydroxide precursor was then cooled in the furnace to obtain an oxide precursor.

[0120] (c) Second heat treatment The oxide precursor obtained in step (b) was mixed with LiOH (Li / (Li-excluded metal) molar ratio=1.3) as a lithium compound to prepare a mixture. Next, the mixture was heat-treated for 8 hours while maintaining the temperature at 1,000°C in a sintering furnace in an O2 atmosphere at a rate of 2°C / min, and then cooled in the furnace to finally obtain a positive electrode active material including a lithium manganese-based oxide.

[0121] Comparative Example 3 A positive electrode active material was prepared in the same manner as in Example 1, except that in step (c), 0.5 mol % of Nb2O3 was used instead of 0.5 mol % of MoO3.

[0122] Manufacturing Example 2. Manufacturing of lithium secondary batteries A positive electrode slurry was prepared by dispersing 90 wt% of the positive electrode active material prepared in Preparation Example 1, 5.5 wt% of carbon black, and 4.5 wt% of PVDF binder in 30 g of N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was uniformly applied to a thin aluminum film having a thickness of 15 μm and dried in a vacuum at 135° C. to prepare a positive electrode for a lithium secondary battery.

[0123] A coin battery was fabricated using a lithium foil as a counter electrode for the positive electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) as a separator, and an electrolyte of LiPF6 at a concentration of 1.15 M in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7.

[0124] Experimental Example 1: Analysis of the properties of the positive electrode active material Lithium manganese oxide was separated from each of the positive electrode active materials prepared in Preparation Example 1, and then photographed with a scanning electron microscope to obtain SEM images. Figures 1 to 3 are SEM images of the lithium manganese oxide contained in the positive electrode active materials according to Example 1, Comparative Example 1, and Comparative Example 2.

[0125] Using an Image Analyzer program, 100 primary particles were selected from the SEM images of the lithium manganese-based oxides contained in the positive electrode active materials according to Examples 1 to 3 and Comparative Examples 1 to 3, and then the average particle size of each primary particle was measured and the average value thereof was calculated.

[0126] Next, 3 g of each of the positive electrode active materials prepared in Preparation Example 1 was weighed out and placed in a pelletizer, and pressed at 4.5 tons for 5 seconds, and the press density was measured.

[0127] The measurement results are shown in Table 1 below.

[0128] [Table 1]

[0129] Experimental Example 2: Composition analysis of positive electrode active material After the lithium manganese oxide was separated from the positive electrode active material of Example 1, the lithium composite oxide was subjected to cross-section processing using an FIB (Ga-ion source), and a cross-sectional SEM image was taken using a scanning electron microscope.

[0130] Next, molybdenum, a target transition metal present inside and on the surface of the primary particles, was mapped through EDX analysis of the lithium manganese oxide identified from the cross-sectional SEM image.

[0131] FIG. 4 is a cross-sectional SEM image of the lithium manganese-based oxide contained in the positive electrode active material according to Example 1, and FIG. 5 is an image of molybdenum mapping (area with high shading density) in the cross-sectional SEM image of FIG. 4 through EDX analysis.

[0132] 5, it can be seen that molybdenum is present on at least a portion of the surface of the primary particles constituting the lithium manganese-based oxide. This result means that a portion of MoO3 used as a flux for crystal growth of the primary particles is present as molybdenum oxide and / or lithium molybdenum oxide on the surface of the primary particles.

[0133] In addition, there is a region that is partially mapped in red within the region corresponding to the inside of the primary particles constituting the lithium manganese-based oxide, which means that molybdenum derived from MoO3 used as a flux for crystal growth of the primary particles is present as a dopant in the primary particles.

[0134] Experimental Example 3: Evaluation of the electrochemical properties of lithium secondary batteries The lithium secondary battery (coin cell) manufactured in Manufacturing Example 2 was subjected to a charge-discharge experiment at 25° C., voltage range of 2.0 V to 4.6 V, and discharge rate of 0.1 C to 5.0 C using an electrochemical analyzer (Toyo, Toscat-3100) to measure the initial charge capacity, initial discharge capacity, initial reversible efficiency, and rate capability (rate capability (C-rate)).

[0135] In addition, the same lithium secondary battery was charged and discharged 50 times at 25°C and within a driving voltage range of 2.0 V to 4.6 V at 1 C / 1 C, and then the ratio of the discharge capacity at the 50th cycle to the initial capacity (cycle capacity retention rate; capacity retention) and the retention rate of the average discharge voltage at the 50th cycle to the average discharge voltage at the 1st cycle (average discharge voltage retention rate) were measured.

[0136] The measurement results are shown in Tables 2 and 3 below.

[0137] [Table 2]

[0138] [Table 3]

[0139] Referring to the results in Tables 2 and 3, it can be seen that the positive electrode active materials according to Examples 1 to 3 have improved discharge characteristics such as initial discharge capacity, discharge capacity ratio, etc., compared to the positive electrode active material according to Comparative Example 1, as the crystal growth of primary particles is promoted by using a flux containing molybdenum.

[0140] Comparing the positive electrode active materials of Examples 1 to 3, in the case of Example 3 in which a relatively small amount of flux containing molybdenum was used, the degree of crystal growth of the primary particles was lower than that of the positive electrode active material of Example 1. As a result, it was confirmed that the discharge capacity (1C-rate) and the discharge capacity ratio (5C / 0.1C) were slightly lower than those of the lithium secondary battery using the positive electrode active material of Example 1.

[0141] Also, in the case of Example 2, in which a relatively large amount of flux containing molybdenum was used, there was no significant difference in the degree of crystal growth compared to the positive electrode active material of Example 1, but it was confirmed that as the amount of flux used increased, the discharge capacity (1C-rate) and the discharge capacity ratio (5C / 0.1C) were slightly lower than those of the lithium secondary battery using the positive electrode active material of Example 1. It is believed that this result is due to the fact that as the content of remaining molybdenum in the lithium manganese-based oxide increased, the content of active metal elements in the lithium manganese-based oxide decreased.

[0142] In addition, it can be seen that the lithium secondary battery using the positive electrode active material according to Comparative Example 2, which includes primary particles in which the crystal growth is promoted by increasing the second heat treatment temperature instead of using a separate flux, exhibits an initial discharge capacity and initial heating efficiency similar to those of the positive electrode active materials according to Examples 1 to 3. However, it can be seen that the cycle capacity retention rate and the discharge capacity rate of the lithium secondary battery using the positive electrode active material according to Comparative Example 2 are lower than those of the lithium secondary battery using the positive electrode active material according to Examples 1 to 3.

[0143] In addition, in the case of the lithium secondary battery using the positive electrode active material of Comparative Example 3 in which the crystal growth of primary particles was promoted by using a flux containing niobium instead of molybdenum, it was confirmed that the initial charge / discharge capacity and the discharge capacity ratio were lower than those of the lithium secondary batteries using the positive electrode active materials of Examples 1 to 3.

[0144] That is, the above results are due to the fact that the use of a flux containing molybdenum promotes the crystal growth of the primary particles constituting the lithium manganese oxide, and at the same time, a portion of the molybdenum used as the flux exists as a dopant in the lithium manganese oxide or as an oxide on the surface of the primary particles, resulting in the formation of rLi2Mn 1-a Mo aIt can be confirmed that this is due to the mitigation and / or prevention of the decrease in charge-transfer and / or diffusion (i.e., surface kinetic) of Li ions on the surface of the primary particles by inducing electrical activation of O3.

[0145] Although the embodiments of the present invention have been described above, a person having ordinary knowledge in the art may modify and change the present invention in various ways by adding, changing, deleting or adding elements without departing from the concept of the present invention described in the claims, and this may also be considered to be within the scope of the claims of the present invention.

Claims

1. A positive electrode active material comprising a lithium-excess lithium-manganese-based oxide containing at least lithium, nickel, manganese and molybdenum, The lithium manganese-based oxide comprises at least one primary particle, The lithium manganese oxide has a primary particle having an average particle size of 0.4 μm to 3.0 μm.

2. The positive electrode active material according to claim 1 , wherein the lithium manganese-based oxide contains the molybdenum as a dopant.

3. 2. The positive electrode active material of claim 1, wherein the lithium manganese-based oxide contains 0.02 mol % to 5.0 mol % of molybdenum based on all metal elements excluding lithium.

4. The positive electrode active material of claim 1 , wherein the lithium manganese-based oxide is represented by the following Chemical Formula 1: [Chemical formula 1] rLi 2 Mn 1-a Mo a O 3 ・(1-r)- b Ni x Co y Mn z Mo z′ M1 1-(x+y+z+z′) O 2 Where: M1 is at least one selected from Nb, Fe, Cr, V, Cu, Zn, Sn, Mg, Ru, Al, Ti, Zr, B, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si and Bi; 0<r≦0.7, 0≦a<0.2, 0<b≦1, 0<x≦1, 0≦y<1, 0<z<1, 0<z'<0.2 and 0<x+y+z+z'≦1.

5. 2. The positive electrode active material according to claim 1, wherein the positive electrode active material has a compressed density of 2.8 g / cc or more under a pressure of 4.5 tons.

6. 2. The positive electrode active material according to claim 1, wherein at least one metal oxide selected from molybdenum oxide and lithium molybdenum oxide is present on at least a portion of the surface of the lithium manganese oxide.

7. The positive electrode active material according to claim 1 , wherein at least one metal oxide represented by the following chemical formula 2 is present on at least a portion of the surface of the lithium manganese-based oxide: [Chemical formula 2] <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> d <h2 style=";text-align:left;direction:ltr"> 12<h2 style=";text-align:left;direction:ltr"> e <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> f Where: M2 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd; 0≦d≦8, 0<e≦8, and 2≦f≦13.

8. A positive electrode comprising the positive electrode active material according to claim 1 .

9. A lithium secondary battery using the positive electrode according to claim 8.

Citation Information

Patent Citations

  • Preparation method for lithium-rich manganese-based positive electrode material of lithium ion battery

    CN105932233A

  • Lithium transition metal compound powder, its production method, spray dried product being baking precursor of the powder, positive electrode for lithium secondary battery using the product, and lithium secondary battery

    JP2008305777A

  • Lithium ion secondary battery, and method for manufacturing positive electrode active material for lithium ion secondary battery

    JP2013114815A

  • Cathode material for lithium batteries

    US20130230780A1

  • Lithium transition metal-based compound powder for positive electrode material in lithium rechargeable battery, method for manufacturing the powder, spray dried product of the powder, firing precursor of the powder, and positive electrode for lithium rechargeable battery and lithium rechargeable battery using the powder

    WO2007116971A1